Polyphenol and Anthocyanin Composition and Activity of Highland Barley with Different Colors - Jin, Hui-Min; Dang, Bin; Zhang, Wen-Gang; Zheng, Wan-Cai; Yang, Xi-Juan (Molecules (Basel, Switzerland), 2022)
In this research, the composition of free phenols, bound phenols, and anthocyanins and their in vitro antioxidant activity and in vitro α-glucosidase inhibiting activity were observed in different barley colors. The outcomes revealed that the contents of total phenols (570.78 mg/100 gDW), total flavonoids (47.08 mg/100 gDW), and anthocyanins (48.07 mg/100 g) were the highest in purple barley. Furthermore, the structure, composition, and concentration of phenolics differed depending on the colors of barley. The types and contents of bound total phenolic acids and flavonoids were greater than those of free total phenolic acids and flavonoids. The main phenolic acids in blue barley were cinnamic acid polyphenols, whereas in black, yellow, and purple barley, benzoic acid polyphenols were the main phenolic acids, and the main types of flavonoids in black and blue barley were chalcones and flavanones, respectively, whereas flavonol was the main type of flavonoid in yellow and purple barley. Moreover, cornflower pigment-3-glucoside was the major anthocyanin in blue, yellow, and purple barley, whereas the main anthocyanin in black barley was delphinidin-3-glucoside. The dark color of barley indicated richness in the anthocyanins. In addition, the free polyphenol fractions had stronger DPPH and ABTS radical scavenging capacity as compared to the bound ones. In vitro α-glucosidase-inhibiting activity was greater in bound polyphenols than in free polyphenols, with differences between different varieties of barley. Purple barley phenolic fractions had the greatest ABTS radical scavenging and iron ion reduction capacities, as well as the highest α-glucosidase-inhibiting activity. The strongest DPPH radical scavenging capacity was found in yellow barley, while the strongest in vitro α-glucosidase-inhibiting activity was found in anthocyanins isolated from black barley. Furthermore, in different colors of barley, there was a strong association between the concentration of specific phenolic compounds and antioxidant and α-glucosidase-inhibiting activities. The outcomes of this study revealed that all colored barley seeds tested were high in phenolic compounds, and had a good antioxidant impact and α-glucosidase-inhibiting activity. As a result, colored barley can serve as an antioxidant and hypoglycemic food. Polyphenols extracted from purple barley and anthocyanins extracted from black barley stand out among them.